Facile Preparation of Carbon Nanotube-Cu(2)O Nanocomposites as New Catalyst Materials for Reduction of P-Nitrophenol - Feng, Yao (Nanoscale Res Lett, 2019)
The effective synthesis and self-assembly of nanocomposites were of key importance for a broad range of nanomaterial applications. In this work, new carbon nanotube (CNT)-Cu(2)O nanocomposites were successfully synthesized via a facile approach. CNT was selected as the anchoring substrate to load Cu(2)O nanoparticles to prepare composite catalysts with well stability and good reusability. It is discovered that the prepared CNT-Cu(2)O nanocomposite materials could be effectively controlled via regulating preparation temperature and time without the use of any stabilizing agents. The nanostructures of synthesized composites were well characterized by many techniques, such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). And the prepared CNT-Cu(2)O nanocomposites with optimized preparation conditions as new catalyst displayed excellent catalytic performance on the reduction reaction of p-nitrophenol, demonstrating potential applications for environmental governance and composite materials.